From Trauma to Strength: Psychological Resilience in Individuals Who Experienced Domestic Violence in Childhood - Anggi There Meyolla Manullang; Arthur Huwae (Bulletin of Counseling and Psychotherapy, 2026)
Experiences of domestic violence during childhood can leave long-term psychological impacts that affect individuals into adulthood. This study aims to describe a portrait of resilience in individuals with childhood trauma resulting from experiences of domestic violence. The research employed a qualitative approach using descriptive phenomenological analysis involving five participants aged 18–30 who had experienced domestic violence since childhood. The findings indicate that despite experiencing profound emotional trauma, participants were able to develop resilience through internal strengths such as hope, responsibility, spirituality, and the ability to forgive, supported by external factors including extended family, friends, and safe environments. The process of resilience appeared unique to each individual and developed dynamically in accordance with their life experiences. In addition, factors such as temperament, cultural values, religious coping, and age were found to influence the adaptation processes they underwent. These findings emphasize the importance of supportive environments and psychological interventions that take into account personal backgrounds and socio-cultural contexts in helping survivors of domestic violence recover and lead healthier and more meaningful lives.